2019
DOI: 10.25248/reas.e1438.2019
|View full text |Cite
|
Sign up to set email alerts
|

Qualidade de vida das gestantes de baixo risco de Teresina – PI

Abstract: Objetivo: avaliar a qualidade de vida das gestantes de baixo risco. Métodos: pesquisa quantitativa, descritiva e transversal realizada com 250 gestantes através de questionário sociodemográfico e Índice de Qualidade de Vida de Ferrans & Powers. Resultados: as gestantes tinham entre 19 e 24 anos, parceiro fixo, pardas, religião católica, renda média mensal de 1 a 2 salários, desempregada, 2º grau completo; já tem filho, sem história de abortos, sem planejamento gestacional e intercorrências gestacionais. Pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
2
0
2

Year Published

2022
2022
2023
2023

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 0 publications
0
2
0
2
Order By: Relevance
“…Older age in pregnant women can positively affect health-related QoL; given their various experiences, these women are able to develop more effective methods of coping with adversity. 13 A study carried out with 261 pregnant women from public and private services in the state of Ceara, Brazil, showed a better QoL in older pregnant women. 14 However, a systematic review of 37 articles showed that advanced maternal age could relate to a reduced QoL of pregnant women.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Older age in pregnant women can positively affect health-related QoL; given their various experiences, these women are able to develop more effective methods of coping with adversity. 13 A study carried out with 261 pregnant women from public and private services in the state of Ceara, Brazil, showed a better QoL in older pregnant women. 14 However, a systematic review of 37 articles showed that advanced maternal age could relate to a reduced QoL of pregnant women.…”
Section: Discussionmentioning
confidence: 99%
“…In the present study, women older than 35 years presented better QoL averages. Older age in pregnant women can positively affect health‐related QoL; given their various experiences, these women are able to develop more effective methods of coping with adversity 13 . A study carried out with 261 pregnant women from public and private services in the state of Ceara, Brazil, showed a better QoL in older pregnant women 14 .…”
Section: Discussionmentioning
confidence: 99%
“…(18,19) Estudo que avaliou a QV de gestantes de baixo risco em Teresina, obteve escore de QV total igual a 23,9 e, portanto inferior ao presente estudo. (20) Outro que comparou a QV de gestantes com e sem disfunção sexual apontou em seus resultados que gestantes com disfunção sexual tiveram menor escore de QV total (22,2), enquanto gestantes sem disfunção sexual obtiveram maior escore de QV total (24,2). (21) Na Paraíba, estudo comparou a QV de gestantes com e sem hipertensão arterial e o resultado mostrou menor escore de QV total nas gestantes hipertensas (20,15) e maior escore de QV total nas gestantes não hipertensas (21,36).…”
Section: Discussionunclassified
“…(20) Outro que comparou a QV de gestantes com e sem disfunção sexual apontou em seus resultados que gestantes com disfunção sexual tiveram menor escore de QV total (22,2), enquanto gestantes sem disfunção sexual obtiveram maior escore de QV total (24,2). (21) Na Paraíba, estudo comparou a QV de gestantes com e sem hipertensão arterial e o resultado mostrou menor escore de QV total nas gestantes hipertensas (20,15) e maior escore de QV total nas gestantes não hipertensas (21,36). (22) Levantamento da QV de puérperas realizado em um hospital de ensino, na cidade de Uberaba, Estado de Minas Gerais, também encontrou menor escore de QV (22,3) no domínio Socioeconômico e maior escore de QV (27,6) no domínio Família, revelando a importância do apoio familiar às 9,7% das puérperas que participaram da pesquisa e eram adolescentes.…”
Section: Discussionunclassified